107k views
2 votes
I need help for the solution​

I need help for the solution​-example-1

1 Answer

1 vote

Answer:


\boxed{ \ dY_t=(2\theta+2\psi Y_t+\phi^2)dt+2\phi √(Y_t)dW_t\ }

Explanation:

it is a long time I have not applied Ito's lemma

I would say the following

for
f(x)=x^2

f'(x)=2x

f''(x)=2

so using Ito's lemma we can write that


dY_t=2V_tdV_t+\phi^2dt


dY_t=2(\theta+\psi V_t^2)dt+2\phi V_tdW_t+\phi^2dt


dY_t=(2\theta+2\psi V_t^2+\phi^2)dt+2\phi V_tdW_t

so it comes


dY_t=(2\theta+2\psi Y_t+\phi^2)dt+2\phi √(Y_t)dW_t

User Na
by
5.2k points